Mauritius The Drivers of Growth-Can the Past be Extended? - Svirydzenka, Katsiaryna (IMF Working Papers; Working Paper ;, 2014)
Mauritius's economic performance has been called 'the Mauritian miracle' and the 'success of Africa' (Romer, 1992; Frankel, 2010; Stiglitz, 2011), despite difficult initial conditions that led a Nobel Prize Winner in economics to predict stagnation (Meade, 1961). We use growth accounting to analyze the sources of past growth and project potential ranges of growth through 2033. Growth averaged 4 1\2 percent over the past 20 years. Our baseline suggests future growth rates around 3u percent, but growth could reach 4-5 percent with strong pro-active policies including (i) improving investment and savings rates; (ii) improving the efficiency of social spending and public enterprise reforms; (iii) investment in education and education reforms; (iii) labor market reforms; and (iv) further measures to reduce bottlenecks and increase productivity. With policies capable of generating 5 percent growth, Mauritius could reach high-income status in 2021, 4 years earlier than under the baseline.